Effects of microbial organic fertilizers on soil microbial communities and physicochemical properties in tobacco cultivation - Wang, Shengli; Zhang, Bao; Ma, Shangyi; Hao, Jie; Zhang, Lei; Guo, Chunsheng; Hong, Jie; Ding, Hai; Zhang, Yan; Wu, Yuanhua; Wang, Weitao; Sun, Jian; et al. (Frontiers in Environmental Science, 2025)
Introduction: Tobacco, as an economic crop in our country, not only requires changes in cultivation practices but also benefits from reasonable fertilization to enhance yield and quality. Microbial organic fertilizers (MOFs) have received considerable attention in recent years; however, the relationship between the rhizosphere soil microorganisms of tobacco plants and the physicochemical properties of soil with MOFs remains poorly understood.Methods: This study established experimental and control groups, employing a five-point sampling method to collect samples of the rhizosphere soil and tobacco leaves at four different growth stages. High-throughput 16S rRNA gene sequencing was conducted to analyze the microbial community structure, while the physicochemical properties of the soil and the physical characteristics of the tobacco leaves were also examined.Results and Discussion: The results indicated that MOF reduced the uptake of ammonium nitrogen by tobacco at different growth stages, promoted the dispersion of the microbial community, and significantly altered the soil microbial community structure. At the phylum level, Actinobacteriota and Proteobacteria are the first and second dominant bacterial phyla in the soil microbial community. Significantly, during the prosperous growth stage of tobacco, the relative abundance of Actinobacteriota (14.90%) in the control group was lower than that of Proteobacteria (19.87%), whereas in the experimental group, the relative abundance of Actinobacteriota (22.99%) was higher than that of Proteobacteria (22.06%). Furthermore, an assessment of tobacco leaf morphology, yield, and quality demonstrated that the application of MOF resulted in a 21.93% increase in leaf yield and a 27.38% increase in yield value per unit area. Furthermore, nicotine and nitrogen content in the tobacco leaves slightly decreased. In summary, this study demonstrates that MOF can improve soil microbial communities and enhance the quality and yield of tobacco leaves, providing valuable insights into the effects of MOF on altering the physicochemical properties of tobacco soil and improving leaf quality.